Relação entre a Classificação Clínica de White e a Histopatologia das Placentas de Gestantes Diabéticas - Calderon, Iracema De Mattos Paranhos [UNESP]; Lima, César Pereira; Rudge, Marilza Vieira Cunha [UNESP]; De Napoli, Gilberto; Jeckel Neto, Emílio Antonio; Ramos, Maria Delgi [UNESP] (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2000)
Purpose: to analyze the relationship between White's classification and the histopathological, changes occurring in the placentas of diabetic pregnant women, performing a qualitative comparison of histopathological changes in the placentas of nondiabetic pregnant women with those in diabetic ones (classes A and A/B), clinical, short duration (classes B and C), and clinical with vasculopathy (classes D to FRH), studying the influence of the quality of glycemic control and of gestational age on placental changes in the three groups of diabetic pregnant women. Patients and methods: specimens of placentas were collected from all diabetic pregnant women seen between 1991 and 1996 in the Maternity Section of the Hospital das Clínicas, Faculdade de Medicina de Botucatu, stained using the hematoxylin-eosin technique, and submitted to a histopathological examination. The quality of glycemic control was analyzed by the glycemia average of gestation and classified as adequate or inadequate, with a limit of 120 mg/dl. Gestational age was individualized as term and preterm. Results: forty-two newborns (43.3%) were born at term and the remaining were preterm (56.7%). The prematurity rate was higher for women with clinical diabetes (classes B and C; D to FRH). Some histopathological alterations were observed only in placentas from diabetic pregnant women: cystoid degeneration, chorial edema, intima edema, dysmaturity, Hofbauer cell hyperplasia, villitis, ghost cells, two vessels in the umbilical cord, and endarteritis. Conclusions: histopathological changes in the placentas of pregnant women with gestational diabetes (classes A and A/B), clinical, short duration (classes B and C), and clinical with vasculopathy (classes D to FRH) were similar to those in the nondiabetic ones, and, therefore, were independent of White's clinical classification. The histopathological changes in the placentas of pregnant women with gestational diabetes (classes A and A and B), clinical, short duration (classes B and C), and clinical with vasculopathy (classes D to FRH) were not related to gestational age at birth and to the quality of glycemic control of the mother. The comparison between histopathological changes and the increased number of preterm newborns in clinical diabetes, class D to FRH, suggest early placental ageing in clinical diabetes patients.

Objetivo: analisar a relação entre a classificação clínica de White e as alterações histopatológicas de placentas de gestantes diabéticas, comparando, de forma qualitativa, as alterações histopatológicas de placentas de gestantes não-diabéticas e diabéticas gestacionais (classes A e A/B), clínicas de curta duração (classes B e C) e clínicas com vasculopatia (classes D a FRH), no termo e no pré-termo, e de acordo com a qualidade do controle glicêmico na gestação. Pacientes e Métodos: foram colhidas amostras de placentas de todas as gestantes diabéticas, atendidas entre 1991 e 1996 na Maternidade do Hospital das Clínicas da Faculdade de Medicina de Botucatu, coradas pela técnica de hematoxilina-eosina e submetidas a exame histopatológico. A qualidade do controle glicêmico foi analisada pela média glicêmica da gestação e classificada em adequada e inadequada, com limite de 120 mg/dl. A idade da gestação foi individualizada em termo e pré-termo. Resultados: observou-se que 42 recém-nascidos (43,3%) eram de termo e o restante, de pré-termo (56,7%). O índice de prematuridade foi maior nas diabéticas clínicas (classes B e C; D a FRH). Algumas alterações histopatológicas só foram encontradas em placentas de gestantes diabéticas: degeneração cistóide, edema corial, edema da íntima, dismaturidade, hiperplasia das células de Hofbauer, vilite, células fantasmas, dois vasos no cordão umbilical e endarterite. Conclusões: as alterações histopatológicas de placentas de gestantes com diabete gestacional (classes A e A/B), clínico de curta duração (classes B e C) e clínico com vasculopatia (classes D a FRH) foram semelhantes às das não-diabéticas e, portanto, independeram da classificação clínica de White. As alterações histopatológicas de placentas de gestantes diabéticas não se relacionaram com a idade gestacional ao nascimento e com a qualidade do controle glicêmico materno. A comparação entre as alterações histopatológicas e a elevada proporção de recém-nascidos pré-termo nas diabéticas clínicas, classes D a FRH, sugerem amadurecimento placentário precoce nas diabéticas clínicas com vasculopatia.
The Relationship between White's Classification and the Histopathological Changes in the Placentas of Diabetic Pregnant Women
Keywords: Diabetes; Placenta; Prematurity; Diabetes mellitus; Placenta; Prematuridade